Silent cerebral embolisation during TAVI: evolution, predictors and neurocognitive effects. (25th November 2020) - De Carlo, M; Liga, R; Migaleddu, G.M; Scatturin, M; Spaccarotella, C; Fiorina, C; Orlandi, G; De Caro, F; Rossi, M.L; Chieffo, A; Indolfi, C; Reimers, B; et al.
Abstract: Background: Most patients undergoing transcatheter aortic valve implantation (TAVI) develop silent cerebral ischemic lesions (SCIL) detectable at magnetic resonance imaging (MRI). The natural history and clinical relevance of SCIL are not well established. We aimed to assess the characteristics, predictors, evolution, and neurocognitive effects of SCIL. Methods: Cerebral MRI was performed within 7 days before TAVI to assess baseline status and age-related white matter changes (ARWMC) score. MRI was repeated postoperatively to assess the occurrence, location, number and dimensions of SCIL. Patients developing SCIL underwent a third MRI at 3–5 months follow-up. A neurocognitive evaluation was performed before TAVI, at discharge and at 3-month follow-up. Results: Of the 117 patients enrolled, 96 underwent a postprocedural MRI; SCIL were observed in 76% of patients, distributed in all vascular territories, with a median number of 2 lesions, median diameter 4.5 mm, and median total volume 140 mm 3 . Independent predictors of SCIL occurrence were a higher baseline ARWMC score and the use of self-expanding or mechanically-expanded bioprostheses. Among 47 patients who underwent follow-up MRI, only 26.7% of postprocedural SCIL evolved into a gliotic scar. SCIL occurrence was associated with a more pronounced transient neurocognitive decline early after TAVI and with a lower recovery at follow-up. Conclusions: SCIL occur in the vast majority of patients undergoing TAVR and are predicted by a more diffuse white matter damage at baseline and by the use of non-balloon-expandable prostheses. Although most SCIL disappear within months, their occurrence has a limited but significant impact on neurocognitive function. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): unrestricted grants from Edwards Lifesciences SA, Nyon, Switzerland, and from Medtronic Italia SpA, Milan, Italy